2008
DOI: 10.1111/j.1445-6664.2007.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a bioherbicide and glyphosate for controlling hemp sesbania in glyphosate‐resistant soybean

Abstract: The bioherbicidal fungus, Colletotrichum truncatum (Schwein.) Andrus & Moore, was tested at different inoculum concentrations alone and in combination with, prior to or following treatment with different rates of glyphosate (N-[phosphonomethyl]glycine) (Roundup Ultra) for the control of hemp sesbania (Sesbania exaltata [Raf.] Rydb. ex A.W. Hill) in Roundup Ready soybean field plots. Colletotrichum truncatum and glyphosate were applied in all pair-wise combinations of 0, 1.25, 2.5, 5.0, and 10.0 ¥ 10 6 spores m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Monitoring weeds in crop fields [90,91] Use economic thresholds to determine when to apply herbicides [91][92][93] Crop rotation [80,91] Using the biological and chemical control [94,95] Using cultural and chemical control [96] Using mechanical and chemical control [97] Using rotation of herbicides [90,91] Plant cover crops [90,98] Using the tillage, no-tillage or reduced tillage system [90,92] However, there are no more ready-made and generalized solutions without risk of errors. IWM is characterized by reliance on multiple weed management approaches that are firmly underpinned by ecological principles [89].…”
Section: Practices Evaluated In Iwm Studymentioning
confidence: 99%
“…Monitoring weeds in crop fields [90,91] Use economic thresholds to determine when to apply herbicides [91][92][93] Crop rotation [80,91] Using the biological and chemical control [94,95] Using cultural and chemical control [96] Using mechanical and chemical control [97] Using rotation of herbicides [90,91] Plant cover crops [90,98] Using the tillage, no-tillage or reduced tillage system [90,92] However, there are no more ready-made and generalized solutions without risk of errors. IWM is characterized by reliance on multiple weed management approaches that are firmly underpinned by ecological principles [89].…”
Section: Practices Evaluated In Iwm Studymentioning
confidence: 99%
“…MV effectively controls kudzu in the absence of a dew treatment over a wide range of physical, environmental, and field conditions [7]. Reports indicate significant performance improvements of several bioherbicides through additive or synergistic effects of chemicals [11] and we reported synergistic interactions of MV and glyphosate on kudzu and some other weeds [12][13][14]. MV host range tests on various tree species commonly found in natural kudzu infestations indicated most trees were not susceptible to MV [15].…”
Section: Introductionmentioning
confidence: 87%
“…For example, in arable crops, the most obvious targets for a biological control agent are perennial weeds, but the interest in biological control agents for perennial weeds would likely be reduced for GMHT crops. In contrast, research [76,77] has shown that sub-lethal doses of glyphosate can work in synergy with microbial biocontrol agents as the former temporarily stops the growth of the weed allowing time for the latter to establish and inhibit growth.…”
Section: Biological Controlmentioning
confidence: 99%